An exploration of the fertility desires and intentions of men living with HIV in Ontario, Canada. Issue 2 (1st February 2021) - Yudin, Mark H.; Kennedy, V. Logan; Bekele, Tsegaye; Watson, James; Globerman, Jason; McGee, Adam; Djiometio, Joseph Nguemo; Antoniou, Tony; Rourke, Sean B.; Loutfy, Mona
ABSTRACT: Planning families is an important issue within the HIV community. The primary objective of this study was to explore the fertility desires and intentions of men living with HIV (MLWH). A cross-sectional survey containing 77 questions in 10 domains was developed, validated and administered to MLWH. The sample was stratified by sexual orientation, ethnicity, and city of residence. Logistic regression analyses were conducted to determine sociodemographic correlates of intention to have children. 276 men were recruited, of whom 118 (43%) identified as heterosexual and 158 (57%) as gay, bisexual, two-spirit or queer (GBTQ). 133 (45%) men wished and 120 (44%) actually intended to become a parent. Significantly more heterosexual men desired fatherhood (63% vs 37%, p  < .0001) and intended to have children in the future (57% vs. 34%, p  < .0001). Among all men, significant predictors of intention to have children were age ≤40, heterosexual orientation, African/Caribbean/Black ethnicity, living in Toronto, higher household income, and being partnered with an HIV-negative individual. When stratified by sexual orientation, younger age remained a significant correlate for both groups. A significant proportion of heterosexual and GBTQ MLWH desire and intend to become a parent. Health care providers and policy makers must support these individuals in their reproductive parenting needs.